2009
DOI: 10.1593/neo.81686
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-Based Chemogene Therapy for Pancreatic Cancer Using Ad-dCK::UMK GDEPT and TS/RR siRNA Strategies

Abstract: Gemcitabine is a first-line agent for advanced pancreatic cancer therapy. However, its efficacy is often limited by its poor intracellular metabolism and chemoresistance. To exert its antitumor activity, gemcitabine requires to be converted to its active triphosphate form. Thus, our aim was to improve gemcitabine activation using gene-directed enzyme prodrug therapy based on gemcitabine association with the deoxycytidine kinase::uridine monophosphate kinase fusion gene (dCK::UMK) and small interference RNA dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 39 publications
4
63
1
Order By: Relevance
“…Exceptions were PANC-1 and SK-BR-3 cell lines that showed high gemcitabine resistance. The obtained result was comparable with IC 50 values found in the literature 13,14 for standard drugs in 2D assay, taking in account the differences in assay setup (number of cells per well, source and formulation of tested standard drugs, washout period, etc.) higher IC 50 value for MIA-PA-Ca-2 and a lower IC 50 value for MDA-MB-231 and T47D.…”
Section: Differences In Drug Responses Between 2d and 3d Culture Modelssupporting
confidence: 88%
See 1 more Smart Citation
“…Exceptions were PANC-1 and SK-BR-3 cell lines that showed high gemcitabine resistance. The obtained result was comparable with IC 50 values found in the literature 13,14 for standard drugs in 2D assay, taking in account the differences in assay setup (number of cells per well, source and formulation of tested standard drugs, washout period, etc.) higher IC 50 value for MIA-PA-Ca-2 and a lower IC 50 value for MDA-MB-231 and T47D.…”
Section: Differences In Drug Responses Between 2d and 3d Culture Modelssupporting
confidence: 88%
“…IR spectra were recorded on a Perkin-Elmer Spectrum 1 spectrophotometer, with KBr disks. 1 H and 13 C NMR spectra were recorded on Bruker Avance DPX 300 and Bruker Avance DRX 500 spectrometers using TMS as an internal standard in DMSO-d 6 . Mass spectra were recorded on Agilent 1100 series LC/MSD Trap SL.…”
Section: General Methodsmentioning
confidence: 99%
“…Chemogene therapy is effective due to the sensitizing of tumor cells to apoptosis by overexpression of a pro-apoptotic protein, followed by the administration of lower doses of chemotherapeutic drugs, therefore reducing systemic toxicity (21,22). Choi et al (23) found that the combination of adenoviral-mediated IFN-β gene therapy and 5-FU resulted in tumor regression, apoptosis, and improved survival in an established liver metastasis model of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the therapeutic gene can directly kill the cells (diphtheria toxin, [20]), or can render the cells sensitive to certain otherwise non toxic prodrugs (Gene Directed Enzyme Prodrug Therapy, GDEPT, [21]), or based on gemcitabine association with the deoxycytidine kinase::uridine monophosphate kinase fusion gene [22]. The systemic administration of conventional chemotherapies fails to reach sufficiently the pancreatic tumor cells and affects the normal cells.…”
Section: Delivering a Suicide Genementioning
confidence: 99%